Diversity and distribution of fish in the Lokop river, Leuser Ecosystem Area, Indonesia - Furqan Maghfiriadi; Firdus Firdus; M. Ali Sarong; Ilham Zulfahmi; Agung Setia Batubara (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Lokop is one of the villages in Serbajadi District, East Aceh Regency, Aceh Province. The village has a watershed named the river Lokop. This river is located in the Leuser Ecosystem Area which is inhabited by various aquatic biota, especially fish, with the level of diversity and distribution patterns that need to be studied and analyzed conoftened. This study used the purposive sampling method, with the parameters being the level of diversity and distribution patterns of fish in the Lokop river. Data collection was carried out at 5 observation stations based on the typology of river habitat, each station was divided into three substations representing parts of the basin, river bank and river basin approximately 50 m apart. Fish sampling is carried out at each station using a plot of 10 x 10 m2. The number of plots at each station is 9 plots with a total of 45 plots. The results showed that the diversity index (H') value of fish in the Lokop river was 2.39 in the moderate category and the distribution pattern of fish in the Lokop river has a uniform pattern and clusters. Out of a total of 17 species obtained, 8 species (47%) were clustred, 8 species (47%) were uniformly distributed and 1 species (6%) could not be analyzed because only one individual was found.Keywords:FishRiverDiversityDistribution